Sosialisasi dan Pelatihan Pemanfaatan Lahan Pekarangan untuk Tanaman Obat Keluarga (TOGA) di Kampung Kweel Kabupaten Merauke - Wiyan Afriyanto Pamungkas; Yosehi Mekiuw; Mega Ayu Yusuf (Jurnal Pengabdian Kepada Masyarakat Digital, 2023)
Family Medicinal Plants (TOGA) is a plant with medicinal properties and prevention of various diseases. TOGA can be cultivated by the community in their yards to become an alternative family medicine for minor illnesses or to help maintain body stamina. However, the community has not used their yard for planting TOGA intensively. The purpose of this community service activity is to increase the knowledge and understanding of the people of Kweel Village, Elikobel District, Merauke Regency, about the potential of their yards and the benefits of Family Medicinal Plants (TOGA) as ingredients or family medicines to deal with health problems independently (self-care). The method used in this service is to provide socialization and training by making demonstration gardens and giving TOGA tree seedlings to be planted, as well as monitoring and evaluation. The results obtained from this community service are the availability of demonstration gardens and TOGA land planted independently by the community. In addition, the community of Kweel Village also gained insight into the benefits of the TOGA they grew in their yards.Keywords: medicinal plant family (TOGA); socialization; training; yard